An Analysis of Islamic Gravestones in Indonesia: Sites and Islamic Heritage in Bolaang Mongondow, North Sulawesi - Saptaningrum, Irna; Azis, Muhammad Nur Ichsan; Anwar, Hasanuddin; Pristiwanto, Pristiwanto; Djakaria, Salmin (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
The discourse on local Islamic archaeology offers a compelling field of study, particularly when examined in relation to the spread of Islamic teachings. In the historical narrative of Islamization in Indonesia, Bolaang Mongondow was a region significantly influenced by Islamic preaching during the 17th–19th centuries CE (11th–13th centuries AH). Archaeological heritage in the form of material culture plays an important role in illustrating the adaptation of local communities to Islamic traditions. The notion of Islam as a “religion of the ruling elite” also contributed to the conversion of local populations. This study presents an archaeological discourse grounded in a historical approach, supported by tangible material evidence, including gravestones and burial complexes, in Bolaang Mongondow, North Sulawesi. Through morphological and technological analyses, the research aims to identify, interpret, and understand the contextual dynamics of local Islamic culture, thereby contributing to a deeper understanding of the region’s Islamic civilizational heritage. The findings reveal a process of adaptation and acculturation closely intertwined with Islamic ideals and concepts. The artefacts uncovered, particularly those from the Kapulo and Jere sites, serve as concrete evidence of the early development of Islamic civilization in Bolaang Mongondow.